Optimal Solution for OCB Improvement Through Strengthening of Servant Leadership, Creativity, and Empowerment - Andi Hermawan; Widodo Sunaryo; Soewarto Hardhienata (Aptisi Transactions On Technopreneurship (ATT), 2023)
In educational institutions, teachers play a central role in the administrative component. Combined with successfully completing the main tasks described in the job description and feeling that they are doing something special, teachers are the key to the success of an organization. Additional activities that are not directly related to the formal reward system that is applied are called OCB (Organizational Citizenship Behavior). Preliminary research shows that PGRI Bogor Vocational High School (SMK) teachers have little OCB information about variables related to increased OCB. This study aims to discuss the relationship between the increase in teacher OCB with the control variables of leadership, creativity and empowerment. This study uses a correlation analysis technique to determine the relationship between the variables studied and the SITEREM index analysis technique to obtain optimal solutions in increasing teacher OCB. The population of this study was 289 teachers at SMK PGRI Bogor. This population was sampled using the Slovin formula in order to obtain a sample of 168 individuals. Correlation analysis shows that there is a positive correlation between subordinate leadership and OCB with a correlation coefficient ry1 = 0.512, and OCB increases when subordinate leadership is strengthened. Creativity and OCB are positively correlated with a correlation coefficient ry2 = 0.438, and OCB increases with increasing creativity. Empowerment and OCB are positively correlated with a correlation coefficient ry3 = 0.502, and increased empowerment increases OCB. The best solution comes from SITEREM analysis. Therefore, out of 27 indicators, 14 good indicators need to be maintained or further developed, and 13 indicators are still weak and need to be improved. 1) Compassion 2) Humility 3) Integrity 4) Accountability 5) Equality 6) Consistency 7) Ethics 8) Mutual assistance 9) Pride 10) Initiative 11) Openness 12 ) Unique ideas 13) Products 14 ) 1. Listening , 2. Courage, 3. Inspirational Gratitude, 4. Need, 5. Wisdom, 6. Problem Solving, 7. Usefulness, 8. Opportunity, 9th Politeness, 10th Citizenship, 11th Awareness, 12th Sport , 13th Altruism.